2000
DOI: 10.1603/0022-0493-93.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transgenic <I>Bacillus thuringiensis</I> Maize Grain on <I>B. thuringiensis</I>-Susceptible <I>Plodia interpunctella</I> (Lepidoptera: Pyralidae)

Abstract: Percentage survivorship, developmental time, adult body length, and sex ratio of Plodia interpunctella (Hub ner) reared on Þeld-produced grain from sixteen cultivars of maize, Zea mays L., including several transgenic Bacillus thuringiensis (Bt) Berliner hybrids and selected non-Bt isolines, were evaluated under laboratory conditions. Compared with isolines, development was delayed and survivorship reduced for P. interpunctella reared on grain from transgenic hybrids with the CaMV/35s promoter that express Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
5
18
0
4
Order By: Relevance
“…observed with P33V08 and N6800Bt hybrids. These data are in accord with those obtained by Giles et al (2000) who examined survival, development, and body size of P. interpunctella developing on several transgenic Bt hybrids. Angoumois grain moth showed a slight but signiÞcant delay in development with MON 810, but there was no difference with Bt-11 or other Bt lines.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…observed with P33V08 and N6800Bt hybrids. These data are in accord with those obtained by Giles et al (2000) who examined survival, development, and body size of P. interpunctella developing on several transgenic Bt hybrids. Angoumois grain moth showed a slight but signiÞcant delay in development with MON 810, but there was no difference with Bt-11 or other Bt lines.…”
Section: Discussionsupporting
confidence: 90%
“…Adults were not sexed to minimize handling and potentially affecting survival and fecundity. A 1:1 male:female sex ratio was assumed based on previous colony performance and on sex ratio not being skewed by transgenic Bt grain as reported by Giles et al (2000). Indian meal moth and Angoumois grain moth eggs were counted at weekly intervals for 5 wk after introducing adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic cotton plants expressing Bt genes provide excellent protection against lepidopteran insects throughout the season and significantly higher yields in the presence of such pests (Artim 2003). Benefits of transgenic, insect-resistant crops include reduced applications of broad spectrum insecticides (Carpenter et al 2002), increased protection due to season-long control of the target insect pests (Rice and Pilcher 1998), protection of stored grain from insect pests (Giles et al 2000), and lower mycotoxin levels due to reduction of fungal pathogens associated with insect damage (Munkvold et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that emergence and fecundity in two species of stored-product moths, P. interpunctella and S. cerealella, had declined when reared on lepidopteran-specific Bt transgenic maize. In P. interpunctella, this effect can last up to 5 months after harvest (Sedlacek et al, 2001;Giles et al, 2000). In addition, the development time from egg to adult for both sexes had increased when reared on Bt maize (Gryspeirt and Grégoire, 2012).…”
mentioning
confidence: 99%